2007
DOI: 10.1246/bcsj.80.1635
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Conjugate Addition Reactions Using In Situ Metallated Terminal Alkynes and the Development of Novel Chiral P,N-Ligands

Abstract: In this account, new methods for the catalytic and stereoselective conjugate addition of terminal alkynes are described. Our laboratories have disclosed asymmetric addition reactions to aldehydes and imines using a combination of a zinc or copper salt and a terminal alkyne. Under these conditions, terminal alkyne is transformed in situ into an alkynyl metal species. Recently, it was found that these in situ generated alkynyl metal species can undergo conjugate additions to alkylidene malonate-type acceptors. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(25 citation statements)
references
References 105 publications
1
24
0
Order By: Relevance
“…Among phosphine-based ligands, phosphaferrocene-oxazoline ligands L28 [95] may also be included, with the asymmetric induction in the Cu(OTf ) 2 -catalyzed addition of Et 2 Zn to various chalcones at up to 91% ee in the presence of L28a. It should be also noted that Carreira et al [10] have utilized chiral phosphines as a ligand for the Cu-catalyzed enantioselective addition of terminal alkynes to Meldrum's acid derivatives.…”
Section: Phosphinesmentioning
confidence: 99%
“…Among phosphine-based ligands, phosphaferrocene-oxazoline ligands L28 [95] may also be included, with the asymmetric induction in the Cu(OTf ) 2 -catalyzed addition of Et 2 Zn to various chalcones at up to 91% ee in the presence of L28a. It should be also noted that Carreira et al [10] have utilized chiral phosphines as a ligand for the Cu-catalyzed enantioselective addition of terminal alkynes to Meldrum's acid derivatives.…”
Section: Phosphinesmentioning
confidence: 99%
“…In this study, we envisioned simultaneous activation of both reaction partners by using the soft Lewis acid/hard Brønsted base cooperative catalyst, which can be represented by a catalytic asymmetric conjugate addition of soft Lewis basic a,b-unsaturated thioamides as the Abstract: A detailed study of the direct catalytic asymmetric conjugate addition of terminal alkynes to a,b-unsaturated thioamides is described. A soft Lewis acid/hard Brønsted base cooperative catalyst, comprising [CuA C H T U N G T R E N N U N G (CH 3 CN) 4 ]PF 6 , bisphosphine ligand, and Li(OC 6 H 4 -p-OMe) simultaneously activated both substrates to compensate for the low reactivity of copper alkynylide. A series of control experiments revealed that the intermediate copper-thioamide enolate functioned as a Brønsted base to generate copper alkynylide from the terminal alkyne, thus driving the catalytic cycle through an efficient proton transfer between substrates.…”
Section: Introductionmentioning
confidence: 99%
“…[1] While an umber of efficient reaction systems have been reported on the asymmetric conjugate addition of sp 3 -a nd sp 2 -carbon nucleophiles by use of chiral metal catalysts and organocatalysts, [2] thed evelopment has been slow on the asymmetric introduction of sp-carbon atoms (alkynyl groups). [1] While an umber of efficient reaction systems have been reported on the asymmetric conjugate addition of sp 3 -a nd sp 2 -carbon nucleophiles by use of chiral metal catalysts and organocatalysts, [2] thed evelopment has been slow on the asymmetric introduction of sp-carbon atoms (alkynyl groups).…”
mentioning
confidence: 99%
“…Asymmetric conjugate alkynylation of a,b-unsaturated carbonyl compounds is one of the most efficient methods of producing alkynes bearing stereogenic carbon centers at the propargyl position. [1] While an umber of efficient reaction systems have been reported on the asymmetric conjugate addition of sp 3 -a nd sp 2 -carbon nucleophiles by use of chiral metal catalysts and organocatalysts, [2] thed evelopment has been slow on the asymmetric introduction of sp-carbon atoms (alkynyl groups). Thecatalytic asymmetric conjugate alkynylation has been reported with nickel, [3] copper, [4] rhodium, [5][6][7][8] and other metal [9] complexes as catalysts.A lthough high yields and high enantioselectivities have been reported for some of acyclic a,b-unsaturated carbonyl compounds,t here have been only af ew reports on successful asymmetric alkynylation of cyclic substrates,t ypically 2-cyclohexenone and 2-cyclopentenone.O ne of them is the nickel-catalyzed addition of alkynylaluminum reagents reported by Corey and co-workers,w herein 3-alkynylcyclohexanones were obtained with 85-90 % ee.…”
mentioning
confidence: 99%